All-solid-state battery and application thereof

By using silicon-based active materials and sulfide solid electrolytes in all-solid lithium batteries, the challenges of traditional lithium batteries in high energy density and safety are solved, achieving higher energy density, lower production costs, and better cycling performance and safety.

CN119627190APending Publication Date: 2025-03-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1

Patent Information

Application Number
CN202411822702.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional lithium batteries have challenges in terms of high energy density and safety, especially the graphite negative electrode has reached the bottleneck of capacity development, the interface between metal lithium and sulfide electrolyte is unstable, and the silicon negative electrode faces huge volume expansion problems.

Method used

Silicon-based active materials are used as the negative electrode active substance, including single silicon, with a value particle size D50 of 1 nm to 100 nm. Combined with sulfide solid electrolyte and conductive agent, an all-solid state battery is formed through the design of the negative electrode current collector and the negative electrode active layer.

Benefits of technology

It improves the weight and volume energy density of the battery, reduces production costs, improves the volume expansion effect of silicon materials, and enhances the cycling performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627190A_ABST
    Figure CN119627190A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state battery and application thereof. The all-solid-state battery comprises a positive pole piece and a negative pole piece, the negative pole piece comprises a sulfide solid electrolyte and a silicon-based active material, the silicon-based active material comprises monatomic silicon, and the median particle diameter D50 of the monatomic silicon is 1 nm to 1 [mu] m; and the solid electrolyte membrane is arranged between the positive pole piece and the negative pole piece, and the solid electrolyte membrane comprises the sulfide solid electrolyte. According to the all-solid-state battery and the application thereof provided by the invention, the weight and volume energy density of the battery can be ensured, the volume expansion effect of a silicon material is effectively improved, the interlayer interface influence of the negative pole piece and the solid electrolyte membrane is relieved, and the cycle performance and the safety of the all-solid-state battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to an all-solid-state battery and applications thereof. Background Art

[0002] In the field of modern energy storage technology, lithium batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density and long cycle life, but traditional lithium batteries still face some challenges in terms of high energy density and safety. Sulfide electrolytes have become important materials in the research of all-solid-state lithium batteries due to their high ionic conductivity and good thermal stability. In order to improve the energy density of sulfide all-solid-state batteries, high-nickel layered cathode materials are considered to be the preferred cathode materials. However, selecting suitable anode materials and applying them to sulfide electrolyte membrane systems is crucial to improving energy density and safety.

[0003] The traditional graphite anode has reached the bottleneck of capacity development. Its one-dimensional transmission channel requires a large amount of sulfide electrolyte to construct the ion transmission path, which leads to the electrode being too thick and the ion transmission kinetics being limited. The interface instability between the metal lithium anode and the sulfide electrolyte makes the practical application of metal lithium in sulfide all-solid-state batteries face huge challenges. The silicon anode has a higher specific capacity and a higher lithium insertion platform, but faces a huge volume expansion problem. Summary of the invention

[0004] The present invention proposes an all-solid-state battery and its application. Through the all-solid-state battery and its application provided by the present invention, the weight and volume energy density of the battery can be ensured, the production cost of the all-solid-state battery can be reduced, the volume expansion effect of the silicon material can be effectively improved, the influence of the interlayer interface between the negative electrode plate and the solid electrolyte membrane can be alleviated, and the cycle performance and safety of the all-solid-state battery can be improved.

[0005] To solve the above technical problems, the present invention is implemented through the following technical solutions.

[0006] The present invention provides an all-solid-state battery, comprising at least:

[0007] Positive electrode;

[0008] A negative electrode plate, the negative electrode plate comprises a sulfide solid electrolyte and a silicon-based active material, the silicon-based active material comprises elemental silicon, and the median particle size D of the elemental silicon is 50 1 nm to 1 μm; and

[0009] A solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane includes the sulfide solid electrolyte.

[0010] In one embodiment of the present invention, the median particle size D of the elemental silicon 50 is 1 nm to 100 nm.

[0011] In one embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer provided on one side of the negative electrode current collector. The negative electrode active layer further includes a binder and a conductive agent. The mass ratio of the silicon-based active material, the sulfide solid electrolyte, the binder, and the conductive agent is (50-90):(3-50):(0.1-10):(0.1-10).

[0012] In one embodiment of the present invention, the binder is selected from one or a combination of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinylpyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid, polyurethane, polyvinyl alcohol, sodium alginate, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer, polypropylene emulsion, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, or polyvinylidene fluoride-trifluorochloroethylene copolymer.

[0013] In one embodiment of the present invention, the negative electrode sheet is obtained by the following method:

[0014] Adding the silicon-based active material, the sulfide solid electrolyte, the binder, and the conductive agent into a solvent, dispersing evenly to obtain a negative electrode slurry; and

[0015] Coating the negative electrode slurry on the negative electrode current collector and drying it under vacuum to obtain the negative electrode sheet.

[0016] In one embodiment of the present invention, the chemical formula of the sulfide solid electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb; X is selected from one or more of Cl, Br, or I.

[0017] In one embodiment of the present invention, M is selected from one or more of Sb, In, and Bi, X is selected from Cl, and the value range of b is 0 < b ≤ 0.1.

[0018] In one embodiment of the present invention, the chemical formula of the sulfide solid electrolyte is Lif P 1-g E g S w O g Q z wherein, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2; E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb; Q is selected from one or more of Cl, Br or I.

[0019] In an embodiment of the present invention, E is selected from Mg, Q is selected from Cl, and the value range of g is 0.01 ≤ g ≤ 0.1.

[0020] The present invention also provides an electronic device, including the all-solid-state battery described above.

[0021] In summary, the present invention provides an all-solid-state battery and its application. By using a silicon-based active material as the negative electrode active substance, it can ensure the weight and volume energy density of the battery, reduce the production cost of the all-solid-state battery, and ensure the performance of the all-solid-state battery. It can increase the specific surface area of elemental silicon, increase the contact area between elemental silicon and the conductive agent and the sulfide solid electrolyte, make the electron and ion conduction paths in the entire electrode good, increase the total current density, and reduce the local current density. It can effectively improve the volume expansion effect of the silicon material, alleviate the interlayer interface effect between the negative electrode sheet and the solid electrolyte film, and improve the cycling performance of the all-solid-state battery. It can improve the stability of the sulfide solid electrolyte, alleviate the interfacial reaction between the electrolyte and the positive and negative electrodes, further improve the cycling performance of the battery, and thus extend the service life of the battery. Elemental silicon has better thermodynamic stability with respect to the sulfide solid electrolyte and does not exhibit the dendrite growth problem existing in lithium metal at room temperature. The combination of the silicon-based active material and the sulfide solid electrolyte results in an all-solid-state battery that can stably cycle at a high current density. It can maintain stable morphology and size under high voltage, improving the safety of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.

[0023] Figure 1 The room temperature 1C / 1C long cycling performance graph for the all-solid-state battery in Example 3. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0025] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0026] The technical solution of the present invention is further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides an all-solid-state battery, which includes a positive electrode sheet, a negative electrode sheet, and a solid electrolyte membrane. In the present invention, the all-solid-state battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery, or a cylindrical battery. The present invention does not specifically limit the type and type of the all-solid-state battery.

[0028] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer disposed on one side of the negative electrode current collector, wherein the negative electrode current collector is, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8 μm to 15 μm.

[0029] In one embodiment of the present invention, the negative electrode active layer includes, for example, a silicon-based active material, a sulfide solid electrolyte, a conductive agent, and a binder, wherein the silicon-based active material includes, for example, elemental silicon, and the shape of the elemental silicon is, for example, spherical, and the median particle size D of the elemental silicon is 50 For example, it is 1 nm to 1 μm, where the median particle size D 50 The median particle size D of elemental silicon is the particle size value corresponding to the cumulative distribution percentage reaching 50%. 50 For example, the median particle size D is 1 nm to 100 nm, and for example, 30 nm to 80 nm, so as to improve the volume expansion effect of the silicon-based active material and improve the interface performance. 50For example, it is obtained by dry testing using a HELOS-RODOS type dry laser particle size analyzer. By using a silicon-based active material as the negative electrode active material, compared with lithium resources, Si has a large abundance and low cost, and a battery using a Si negative electrode has a weight and volume energy density comparable to that of lithium metal, which can reduce the production cost of all-solid-state batteries and ensure the performance of all-solid-state batteries. Selecting nanosized elemental silicon can increase the specific surface area of elemental silicon, thereby increasing the contact area between elemental silicon and the conductive agent and sulfide solid electrolyte, enabling good electron and ion conduction paths throughout the electrode, increasing the total current density, and reducing the local current density. Moreover, the nanoscale elemental silicon effectively improves the volume expansion effect of the silicon material and alleviates the interfacial influence between the negative electrode sheet and the solid electrolyte membrane. Compared with micron-sized elemental silicon, the number of stable cycling times is increased by more than 2 times at a current rate of 1C / 1C.

[0030] In one embodiment of the present invention, the chemical formula of the sulfide solid electrolyte (SSE) is selected from, for example, Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z and at least one of the like. Among them, in Li a P 1-b M b S c O d X e 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, etc., and X is selected from at least one of Cl, Br, or I, etc. Further, M is, for example, selected from at least one of Sb, In, or Bi, X is Cl, and the value range of b is, for example, 0 < b ≤ 0.1. Further still, when M is, for example, a +5 valence element, b is, for example, 0.04, and when M is, for example, a +3 valence element, b is, for example, 0.02. By controlling the types of elements M and X and the value range of b in the sulfide solid electrolyte, the stability of the sulfide solid electrolyte can be improved, the cycling performance of the battery can be improved, and thus the service life of the battery can be extended.

[0031] In one embodiment of the present invention, when the chemical formula of the sulfide solid electrolyte is Li f P 1-g E g S w Og Q z When 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, etc., and Q is selected from at least one of Cl, Br, I, etc. Further, E is, for example, Mg, Q is, for example, Cl, and the value range of g is, for example, 0.01 ≤ g ≤ 0.1. Specifically, g is, for example, 0.02. By controlling the type of element E, the type of element Q, and the value range of g in the sulfide solid electrolyte, the stability of the sulfide solid electrolyte can be improved, the cycle performance of the battery can be improved, and thus the service life of the battery can be extended. Elemental silicon has better thermodynamic stability for the sulfide solid electrolyte and does not have the problem of dendrite growth existing in lithium metal at room temperature. Therefore, when the silicon-based active material and the sulfide solid electrolyte are used in combination, the obtained all-solid-state battery can stably cycle at a high current density.

[0032] In an embodiment of the present invention, when preparing the sulfide solid electrolyte, in an atmosphere of an inert gas such as argon, according to the chemical formula of the sulfide solid electrolyte Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z, after the Li source, P source, M source, S source and X source, or the Li source, P source, E source, S source and Q source are uniformly mixed according to stoichiometric ratio, for example, placed in a ball mill for ball milling to obtain a precursor powder, and then the precursor powder is annealed and sintered at a high temperature to obtain a sulfide solid electrolyte. Wherein, the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, the P source is selected from one or more of simple substance P, P2S5, P4S6, PCl5 or PBr5, the M source is selected from one or more of M oxides or M sulfides, the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, the E source is selected from one or more of E oxides or E sulfides, the Q source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, the S source is selected from one or more of simple substance S, Li2S, P2S5, M sulfide or E sulfide, and the O element in the chemical formula comes from the oxide of M or the oxide of E. Wherein, the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1000 rpm, and the ball milling time is, for example, 1 h to 48 h. After ball milling, a precursor powder is obtained, and the precursor powder is calcined at 400° C. to 600° C. for 1 h to 18 h to obtain a sulfide solid electrolyte.

[0033] In one embodiment of the present invention, the conductive agent is selected from at least one of graphite, graphene, conductive carbon black (Super P), nanocarbon fiber (Vapor-grown Carbon Fiber, VGCF) or carbon nanotubes, and for example, conductive carbon black and nanocarbon fiber are selected, and the mass ratio of conductive carbon black to nanocarbon fiber is, for example, 1: (0.1-2), and for example, 1: 1. The binder is selected from, for example, polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane (PU), polyvinyl alcohol (PVA), polyvinyl alcohol (PVB), polyvinyl alcohol (PVA), polyvinyl alcohol (PVP), polyvinyl alcohol (PVA ... Alcohol, PVA), sodium alginate (Sodium Alginate, Alg), ethylene-propylene-diene monomer (EPDM), styrene-butadiene rubber, fluorine rubber (Fluororubber), β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (Polytetrafluoroethylene, PTFE), ethylene-tetrafluoroethylene copolymer (EthyleneTetrafluoroethylene, ETFE), fluorinated ethylene-propylene copolymer (Fluorinated Ethylene Propylene, FEP), perfluoroalkoxy resin (Polyfluoroalkoxy, PFA), polychlorotrifluoroethylene (Polychlorotrifluoroethylene, PCTFE), ethylene-chlorotrifluoroethylene copolymer (Ethylene-chlorotrifluoroethylene Copolymer, ECTFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) or polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), etc. At least one of the above. Furthermore, the binder is, for example, selected from one or more of styrene-butadiene rubber, polyacrylic acid and fluororubber.

[0034] In one embodiment of the present invention, the negative electrode current collector is, for example, copper foil, and the mass ratio of the silicon-based active material, the sulfide solid electrolyte, the binder and the conductive agent is (50-90): (3-50): (0.1-10): (0.1-10). The silicon-based active material, the sulfide solid electrolyte, the binder and the conductive agent are mixed according to the mass ratio, added into a solvent, and dispersed uniformly to obtain a negative electrode slurry. In the negative electrode slurry, the content of the solvent is, for example, 10wt% to 60wt%. The negative electrode slurry is coated on the negative electrode current collector by a wet coating method or an electrostatic spraying method, and vacuum dried to obtain a negative electrode sheet. The solvent is selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, glycol dimethyl ether, dibutyl anisole, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone, and is selected from one or more of toluene, dimethylbenzene, anisole and butyl butyrate. The vacuum drying temperature is, for example, 30°C to 250°C, and the drying time is, for example, 1h to 48h.

[0035] In one embodiment of the present invention, the solid electrolyte membrane is obtained by cold pressing the above-mentioned sulfide solid electrolyte at a pressure of 300MPa to 400MPa, and the thickness of the solid electrolyte membrane is, for example, 100μm to 500μm. The use of the above-mentioned modified sulfide solid electrolyte to prepare the solid electrolyte membrane can alleviate the interface reaction between the electrolyte and the positive and negative electrodes, and the battery cycle stability is greatly improved compared with the unmodified sulfide electrolyte.

[0036] In one embodiment of the present invention, the positive electrode sheet includes, for example, a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric, and the thickness of the positive electrode current collector is, for example, 8 μm to 15 μm.

[0037] In one embodiment of the present invention, the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a conductive agent and a binder, wherein the positive electrode active material is, for example, selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA). The positive electrode electrolyte is, for example, a halide solid electrolyte, the conductive agent is, for example, selected from at least one of graphite, graphene, conductive carbon black, nanocarbon fiber or carbon nanotube, and the binder is, for example, selected from at least one of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid, polyurethane, polyvinyl alcohol, sodium alginate, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer, polypropylene emulsion, polytetrafluorovinylidene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

[0038] In one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is for example Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , the conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1, and the binder is, for example, PTFE. After the positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are uniformly mixed in a mass ratio of, for example, 69:29:1:1, they are compounded with aluminum foil by dry pressing to obtain a positive electrode sheet. The present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder, which can be selected according to actual needs, and the positive electrode current collector can be not provided as needed.

[0039] In one embodiment of the present invention, the above-mentioned positive electrode plate, solid electrolyte membrane and negative electrode plate are placed in sequence, pressed and sealed to obtain an all-solid-state battery. The assembly process of the all-solid-state battery is completed in an inert atmosphere glove box. When manufacturing an all-solid-state battery, high-force pressing and sealing are required to achieve close contact between the electrode and the solid electrolyte membrane. Compared with metallic lithium, which can easily penetrate the solid electrolyte membrane at a pressure greater than 25MPa, causing a short circuit, elemental silicon has a high Young's modulus of 130GPa, and can maintain a stable morphology and size under high pressure, thereby improving the safety of the all-solid-state battery.

[0040] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0041] Example 1

[0042] Preparation of negative electrode sheet: Under argon atmosphere, 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 raw materials were added into a ball mill with a ball-to-material ratio of 30:1 and a rotation speed of 500 rpm. The ball milled the raw materials for 20 h and then sintered the precursor powder at 500 °C for 10 h to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide solid electrolyte.

[0043] D 50 1nm spherical silicon, Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , conductive agent and SBR are mixed in a mass ratio of 72:20:5:3, added to butyl butyrate solvent and dispersed evenly to obtain negative electrode slurry. The content of butyl butyrate in the negative electrode slurry is 50wt%, and the negative electrode slurry is coated on copper foil, vacuum dried at 80°C for 12h, and cut into discs with a diameter of 10mm to obtain negative electrode sheets. Among them, the conductive agent includes Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1.

[0044] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , PTFE are mixed evenly in a mass ratio of 69:29:1:1, and then compounded with aluminum foil by dry pressing, and cut into discs with a diameter of 10 mm to obtain a positive electrode sheet. The conductive agent includes Super P and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1.

[0045] Preparation of solid electrolyte membrane: The above sulfide solid electrolyte was cold pressed at a pressure of 350 MPa to obtain a solid electrolyte membrane with a thickness of 300 μm.

[0046] All-solid-state battery assembly: The positive electrode sheet, solid electrolyte membrane sheet and negative electrode sheet prepared above are stacked in sequence, pressed and sealed, and assembled into an all-solid-state battery.

[0047] Example 2

[0048] D of silicon 50 The thickness is 10 nm, and other operations are consistent with those in Example 1.

[0049] Example 3

[0050] D of silicon 50 The thickness is 50 nm, and other operations are consistent with those in Example 1.

[0051] Example 4

[0052] D of silicon 50 The thickness is 100 nm, and other operations are consistent with those in Example 1.

[0053] Example 5

[0054] D of silicon 50 The other operations are the same as those in Example 1.

[0055] Example 6

[0056] Silicon, Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , the mass ratio of conductive agent and SBR is 52:40:5:3, and other operations are consistent with Example 3.

[0057] Example 7

[0058] Silicon, Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , the mass ratio of conductive agent and SBR is 62:30:5:3, and other operations are consistent with Example 3.

[0059] Example 8

[0060] Silicon, Li 5.5 P 0.96 Sb 0.04 S 4.40 O0.10 Cl 1.5 , the mass ratio of conductive agent and SBR is 82:10:5:3, and other operations are consistent with Example 3.

[0061] Example 9

[0062] Silicon, Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , the mass ratio of conductive agent and SBR is 89:3:5:3, and other operations are consistent with Example 3.

[0063] Example 10

[0064] When preparing the negative electrode plate, SBR was replaced with PVDF, and other operations were consistent with Example 3.

[0065] Embodiment 11

[0066] When preparing the negative electrode sheet, SBR was replaced with PAA, and other operations were consistent with Example 3.

[0067] Example 12

[0068] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Sb2O5 is Li 5.5 P 0.99 Sb 0.01 S 4.475 O 0.025 Cl 1.5 , other operations remain the same as those in Example 3.

[0069] Embodiment 13

[0070] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Sb2O5 is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0071] Embodiment 14

[0072] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Sb2O5 is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 , other operations remain the same as those in Example 3.

[0073] Embodiment 15

[0074] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.48 mol of P2S5, and 0.02 mol of Sb2O5 is Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.3 Br 0.1 I 0.1 , other operations remain the same as those in Example 3.

[0075] Example 16

[0076] The chemical formula of the sulfide solid electrolyte prepared by 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.005 mol In2O3 is Li 5.52 P 0.99 In 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.

[0077] Embodiment 17

[0078] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 3.

[0079] Embodiment 18

[0080] The chemical formula of the sulfide solid electrolyte prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol In2O3 is Li 5.62 P 0.94 In 0.06 S 4.41 O 0.09 Cl 1.5 , other operations remain the same as those in Example 3.

[0081] Embodiment 19

[0082] The chemical formula of the sulfide solid electrolyte prepared by 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol In2O3 is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0083] Embodiment 20

[0084] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.3 Br 0. 1I 0.1 , other operations remain the same as those in Example 3.

[0085] Embodiment 21

[0086] The chemical formula of the sulfide solid electrolyte prepared by 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.005 mol Bi2O3 is Li 5.52 P 0.99 Bi 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.

[0087] Embodiment 22

[0088] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 3.

[0089] Embodiment 23

[0090] The chemical formula of the sulfide solid electrolyte prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol Bi2O3 is Li 5.62 P 0.94 Bi 0.06 S 4.41 O 0.09 Cl 1.5 , other operations remain the same as those in Example 3.

[0091] Embodiment 24

[0092] The chemical formula of the sulfide solid electrolyte prepared by 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol Bi2O3 is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0093] Embodiment 25

[0094] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.3 Br 0. 1I 0.1 , other operations remain the same as those in Example 3.

[0095] Embodiment 26

[0096] The chemical formula of the sulfide solid electrolyte prepared by 2.015 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.01 mol MgO is Li 5.53 P 0.99 Mg 0.01 S 4.49 O 0.01 Cl 1.5 , other operations remain the same as those in Example 3.

[0097] Embodiment 27

[0098] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 , other operations remain the same as those in Example 3.

[0099] Embodiment 28

[0100] The chemical formula of the sulfide solid electrolyte prepared by 2.09 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.06 mol MgO is Li 5.68 P 0.94 Mg 0.06 S 4.44 O 0.06 Cl 1.5 , other operations remain the same as those in Example 3.

[0101] Embodiment 29

[0102] The chemical formula of the sulfide solid electrolyte prepared by 2.15 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.1 mol MgO is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 , other operations remain the same as those in Example 3.

[0103] Embodiment 30

[0104] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.02 mol MgO is Li5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.3 Br 0.1 I0 .1 , other operations remain the same as those in Example 3.

[0105] Comparative Example 1

[0106] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 3.

[0107] Comparative Example 2

[0108] D of silicon 50 The other operations are the same as those in Example 1.

[0109] Comparative Example 3

[0110] The mass ratio of elemental silicon, conductive agent and SBR is 92:5:3, and other operations are consistent with Example 3.

[0111] In Examples 1-30 and Comparative Examples 1-3 of the present invention, different sulfide solid electrolytes and negative electrode sheets are used to prepare all-solid-state batteries, and some characteristics of the sulfide solid electrolytes and negative electrode sheets are shown in Table 1. Under a 25°C environment, the above-prepared all-solid-state battery is subjected to long-cycle charge and discharge, its discharge capacity is measured, and the energy density is calculated. Among them, the working voltage range of the battery test is 2.5V-4.3V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded as 1C discharge capacity. When the battery capacity reaches 80% of the first cycle capacity (80% State of Health, 80% SOH), the test is terminated, and the number of cycles at room temperature is obtained. The test results are shown in Table 2.

[0112] Table 1. Properties of sulfide solid electrolytes and negative electrode sheets in Examples 1-30 and Comparative Examples 1-3

[0113]

[0114] Table 2 Performance test results of all-solid-state batteries in Examples 1-30 and Comparative Examples 1-3

[0115] Group Number of 1C / 1C cycles at room temperature (80% SOH) Example 1 986 Example 2 1045 Example 3 1124 Example 4 1066 Example 5 821 Example 6 1186 Example 7 1178 Example 8 887 Example 9 521 Example 10 1012 Embodiment 11 1023 Example 12 761 Embodiment 13 1015 Embodiment 14 890 Embodiment 15 976 Example 16 755 Embodiment 17 1033 Embodiment 18 937 Embodiment 19 985 Embodiment 20 933 Embodiment 21 741 Embodiment 22 1015 Embodiment 23 919 Embodiment 24 967 Embodiment 25 915 Embodiment 26 745 Embodiment 27 999 Embodiment 28 903 Embodiment 29 816 Embodiment 30 899 Comparative Example 1 136 Comparative Example 2 286 Comparative Example 3 13

[0116] Please refer to Table 1 and Table 2. By comparing Examples 1-5 and Comparative Example 2, it can be seen that as the D of elemental silicon increases 50 As the D of the single-substance silicon increases, the cycle performance of the all-solid-state battery gradually increases, and then gradually decreases. Compared with 10-micron single-substance silicon, the number of stable cycles at a current rate of 1C / 1C has increased by more than 2 times. This is because single-substance silicon with small particles has greater rigidity and a smaller volume expansion coefficient, which is beneficial to improving the cycle performance of silicon-based negative electrode batteries. However, if the single-substance silicon particles are too small, the specific surface area is too large, the contact area with the sulfide solid electrolyte is larger, and the side reactions are more serious, which is not conducive to the battery cycle. Therefore, controlling the D of single-substance silicon is very important. 50 , which can reduce the volume expansion of silicon-based active materials and improve the cycle performance of batteries.

[0117] Please refer to Table 1 and Table 2. From Comparative Example 3, Examples 6-9 and Comparative Example 3, it can be seen that as the mass proportion of elemental silicon in the negative electrode active layer increases, the cycle performance of the lithium-ion battery gradually decreases, but when the elemental silicon is in the range of 52wt% to 72wt%, the performance difference is not large, and the negative electrode plate with a high elemental silicon content is beneficial to improving the energy density of the battery. Therefore, in order to balance the relationship between the battery cycle performance and the battery energy density, a 72wt% elemental silicon content is preferred.

[0118] See also Figure 1 As shown, at a current density of 1C, the all-solid-state battery in Example 3 still has an energy storage capacity of about 155 mAh / g after 1124 cycles, indicating that the combined use of sulfide solid electrolyte and elemental silicon enables the all-solid-state battery to have excellent specific capacity, rate performance, long cycle life and other properties.

[0119] Please refer to Table 1 and Table 2. By comparing Example 3 and Examples 10-11, it can be seen that the cycle performance of the all-solid-state battery is different when different binders are used in the negative electrode active layer. Among them, when the SBR binder is used, the performance of the silicon-based negative electrode plate is optimal.

[0120] Please refer to Table 1 and Table 2. It can be seen from Examples 3 and 12-14 that as the doping amount of the Sb element in the sulfide solid electrolyte increases, the cycle performance of the all-solid-state battery gradually increases and then gradually decreases. It can be seen from Examples 16-19 that as the doping amount of the In element in the sulfide solid electrolyte increases, the cycle performance of the all-solid-state battery gradually increases and then gradually decreases. It can be seen from Examples 21-24 that as the doping amount of the Bi element in the sulfide solid electrolyte increases, the cycle performance of the all-solid-state battery first increases gradually and then gradually decreases. It can be seen from Examples 26-27 that as the doping amount of the Mg element in the sulfide solid electrolyte increases, the cycle performance of the all-solid-state battery first increases gradually and then gradually decreases. This is because when the doping amount in the sulfide solid electrolyte is too low, the improvement effect of the stability of the sulfide solid electrolyte itself is not obvious, and the cycle performance is poor. When the doping amount in the sulfide solid electrolyte is too large, excessive doping will cause excessive lattice distortion, destroy the original crystal structure, and may cause the structural stability of the material to decrease, and the cycle performance of the battery to decrease. Therefore, controlling the doping amount in the sulfide solid electrolyte within an appropriate range and combining it with silicon-based active materials can improve the cycle performance of all-solid-state batteries.

[0121] Please refer to Table 1 and Table 2. Comparing Examples 3 and 15, Examples 17 and 20, Examples 22 and 25, and Examples 27 and 30, it can be seen that when the doping amount of Sb, In, Bi or Mg in the sulfide solid electrolyte is the same, the addition of Br and I elements will reduce the cycle performance of the battery. Comparing Example 5, Example 14, Example 19, Example 24 and Comparative Example 1, it can be seen that when the sulfide solid electrolyte is not doped with elements such as Sb, In, Bi or Mg, the cycle performance of the battery is very poor. Therefore, when the silicon-based active material in this application and the sulfide solid electrolyte provided in this application are used in combination, the cycle performance of the all-solid-state battery can be greatly improved.

[0122] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state batteries, and the all-solid-state battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state battery, and therefore includes the advantages of the above-mentioned all-solid-state battery, which will not be elaborated here.

[0123] In summary, the present invention proposes an all-solid-state battery and its application. By using silicon-based active materials as negative electrode active materials, the weight and volume energy density of the battery can be ensured, the production cost of the all-solid-state battery can be reduced, and the performance of the all-solid-state battery can be ensured. It can increase the specific surface area of ​​elemental silicon, increase the contact area between elemental silicon and the conductive agent and the sulfide solid electrolyte, make the electron and ion conduction paths in the entire electrode good, improve the total current density, and reduce the local current density. It can effectively improve the volume expansion effect of silicon materials, alleviate the interlayer interface influence of the negative electrode plate and the solid electrolyte membrane, and improve the cycle performance of the all-solid-state battery. It can improve the stability of the sulfide solid electrolyte, alleviate the interface reaction between the electrolyte and the positive and negative electrodes, further improve the cycle performance of the battery, and thus extend the service life of the battery. Elemental silicon has better thermodynamic stability to the sulfide solid electrolyte, and there will be no dendrite growth problem of lithium metal at room temperature. The combination of silicon-based active materials and sulfide solid electrolytes can obtain a stable cycle of the all-solid-state battery at high current density. It can maintain the stability of the morphology and size under high pressure, and improve the safety of the all-solid-state battery.

[0124] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0125] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. An all-solid-state battery, characterized in that: include: Positive electrode; A negative electrode plate, the negative electrode plate comprises a sulfide solid electrolyte and a silicon-based active material, the silicon-based active material comprises elemental silicon, and the median particle size D of the elemental silicon is 50 1nm~1μm; as well as A solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane includes the sulfide solid electrolyte.

2. The all-solid-state battery according to claim 1, characterized in that: The median particle size D of the elemental silicon 50 It is 1nm~100nm.

3. The all-solid-state battery according to claim 1, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode active layer arranged on one side of the negative electrode current collector, the negative electrode active layer also includes a binder and a conductive agent, and the mass ratio of the silicon-based active material, the sulfide solid electrolyte, the binder and the conductive agent is (50-90): (3-50): (0.1-10): (0.1-10).

4. The all-solid-state battery according to claim 3, characterized in that: The binder is selected from one or a combination of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid, polyurethane, polyvinyl alcohol, sodium alginate, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer, polypropylene emulsion, polytetrafluorovinylidene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

5. The all-solid-state battery according to claim 3, characterized in that: The negative electrode plate is obtained by the following method: Adding the silicon-based active material, the sulfide solid electrolyte, the binder and the conductive agent into a solvent and dispersing them uniformly to obtain a negative electrode slurry; and The negative electrode slurry is coated on the negative electrode current collector and vacuum dried to obtain the negative electrode sheet.

6. The all-solid-state battery according to claim 1, characterized in that: The chemical formula of the sulfide solid electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb; X is selected from one or more of Cl, Br or I.

7. The all-solid-state battery according to claim 6, characterized in that: M is selected from one or more of Sb, In and Bi, X is selected from Cl, and the value range of b is 0 <b≤0.1。 8. The all-solid-state battery according to claim 1, characterized in that: The chemical formula of the sulfide solid electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2; E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn, or Pb; Q is selected from one or more of Cl, Br, or I.

9. The all-solid-state battery according to claim 8, characterized in that: E is selected from Mg, Q is selected from Cl, and the value range of g is 0.01≤g≤0.

1.

10. An electronic device, characterized in that: An all-solid-state battery comprising any one of claims 1 to 9.

Citation Information

Patent Citations

  • Inorganic sulfide solid electrolyte and preparation method thereof

    CN113471521A

  • Silicon negative electrode active material, preparation method thereof and application of silicon negative electrode active material in all-solid-state battery

    CN116031377A

  • Solid-state battery and preparation method thereof

    CN116525966A

  • All-solid-state battery, preparation method thereof and vehicle

    CN118054066A

  • Negative electrode composite material, negative electrode pole piece, all-solid-state battery and preparation method

    CN118352510A

Cited By

  • All-solid-state battery negative plate, all-solid-state battery and preparation method

    CN120511265A